Anthocyanin pigments in strawberry - Lopes-da-Silva, M.F. (2011)
The anthocyanin composition was analysed in strawberry fruits from five different cultivars (cv. Eris, Oso Grande, Carisma, Tudnew and Camarosa). Twenty-five defined anthocyanin pigments were detected, most of them containing Pelargonidin (Pg) as aglycone; some cyanidin (Cy) derivatives were also found. Glucose and rutinose were the usual substituting sugars, although arabinose and rhamnose were also tentatively identified; some minor anthocyanins showed acylation with aliphatic acids. A relevant aspect was the detection of anthocyanin-derived pigments, namely 5-carboxypyranopelargonidin-3-glucoside and four condensed pigments containing C–C linked anthocyanin (Pg) and flavanol (catechin and afzelechin) residues. Total anthocyanin content ranged between 200 and 600mg/kg, with Pg 3-gluc constituting 77–90% of the anthocyanins in the strawberry extracts followed by Pg 3-rut (6–11%) and Cy 3-gluc (3–10%). A notable variability was found among the anthocyanin concentrations in samples of a same variety and harvest, indicating a strongly influence of the degree of maturity, edaphic-climatic factors and post-harvest storage.